Nano-Biomechanical Investigation of Phosphatidylserine-Mediated Ebola Viral Attachment via Human Gas6 and Axl - Decheng Hou; Qian Mu; Weixuan Chen; Wenpeng Cao; Xiaohui Frank Zhang (Viruses)
The Ebola virus is a deadly pathogen that has been threatening public health for decades. Recent studies have revealed alternative viral invasion routes where Ebola virus approaches cells via interactions among phosphatidylserine (PS), PS binding ligands such as Gas6, and TAM family receptors such as Axl. In this study, we investigate the interactions among phosphatidylserine on the Ebola viral-like particle (VLP) membrane, human Gas6, and human Axl using atomic force microscope-based single molecule force spectroscopy to compare their binding strength and affinity from a biomechanical perspective. The impact of calcium ions on their interactions is also studied and quantified to provide more details on the calcium-dependent phosphatidylserine-Gas6 binding mechanism. Our results indicate that, in the presence of calcium ions, the binding strengths of VLP-Gas6 and VLP-Gas6-Axl increase but are still weaker than that of Gas6-Axl, and the binding affinity of VLP-Gas6 and VLP-Gas6-Axl is largely improved. The binding strength and affinity of Gas6-Axl basically remain the same, indicating no impact in the presence of calcium ions. Together, our study suggests that, under physiological conditions with calcium present, the Ebola virus can utilize its membrane phosphatidylserine to dock on cell surface via Gas6-Axl bound complex.